Artificial Life 13 2012
DOI: 10.7551/978-0-262-31050-5-ch022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Local Communication and Topology on Collective Movement Initiation

Abstract: Collective movement in autonomous systems, such as a team of robots, are frequently implemented using complex interaction rules and have significant communication requirements. These restrictions frequently relegate such systems to static, simplified environments. In contrast, collective movements in natural systems consistently occur in dynamic, complex environments in which significant communication is either impractical or impossible, and have been successfully modeled using simple, local interaction rules.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Furthermore, larger groups resulted in faster times, regardless of the environment. This was due to the fact that, as previous work has shown, larger groups increased the likelihood of a successful initiation [21,22]. Percentages indicate the fraction of agents that reached a particular, preferred destination.…”
Section: Results and Analysismentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, larger groups resulted in faster times, regardless of the environment. This was due to the fact that, as previous work has shown, larger groups increased the likelihood of a successful initiation [21,22]. Percentages indicate the fraction of agents that reached a particular, preferred destination.…”
Section: Results and Analysismentioning
confidence: 94%
“…The original model was only evaluated with a group size of 10, but previous results have shown that the success of collective movements increases as the group size is increased, with most success differences present in group sizes of 50 or less [21]. As such, evaluating different group sizes presented an opportunity to evaluate the effects of conflict with different group dynamics.…”
Section: Numerical Implementationmentioning
confidence: 98%
“…The original model only used a group size of 10, but other work has shown that the success of collective movement initiations increases as the group size is increased, with most differences present in group sizes of 50 or less [3]. As such, evaluating different group sizes presents an opportunity to evaluate the effects of conflict with different group dynamics.…”
Section: Numerical Implementationmentioning
confidence: 96%
“…The original model was only evaluated with a group size of 10, but other work has shown that the success of collective movement initiations increases as the group size is increased, with most success differences present in group sizes of 50 or less and diminishing effects beyond a group size of 100 [2]. As such, evaluating different group sizes presents an opportunity to evaluate the effects of personality with different group dynamics.…”
Section: Numerical Implementationmentioning
confidence: 98%